Description of the Implementation of Oral Hygiene Measures for Stroke Patients at Bhayangkara Hospital Makassar - Thalib, Abd. Herman Syah (Jurnal Perilaku Kesehatan Terpadu, 2022)
This research generally aims to determine the description of the implementation of oral hygiene in stroke patients at Bhayangkara Hospital Makassar. This research uses descriptive research with observational methods. The number of samples in this study was 30 respondents. Sample selection was carried out using Accidental Sampling. Data was collected using a check list observation questionnaire, analyzed using the SPSS 16 program. The results of the analysis showed that most of the nurses' actions in providing oral hygiene had been carried out correctly, supported by data of 60.0%, and the majority of patients had teeth and mouths that were correct. net, this statement is supported by data of 60.0%. It can be concluded that the nurses' actions in providing oral hygiene have been carried out appropriately and the majority of patients have clean teeth and mouths. For further research, more respondents and better measuring tools are needed to increase the accuracy of the research results.